IMPLEMENTASI BUDAYA KERJA CORE VALUE APARATUR SIPIL NEGARA (ASN) BERAKHLAK - Lilis Siti Rohmah; Gerda Cendana; R. Rindu Garvera (Majalah Ilmiah Dinamika Administrasi (MIDA), 2023)
Today the government is required to organize clean, service-oriented, and efficient governance. However, in reality, corruption, collusion, and nepotism have always been problems in government that are difficult to eliminate. Many factors affect the decline in the quality of governance, one of which is the work culture. Work culture is the behavior or habits of employees in the work environment. Therefore, to improve employee performance in government administration, an effective work culture is needed so that it can have a positive impact on employee performance. In this case, the Regional Government of the City of Banjar applies the work culture of the Core Value ASN BerAKHLAK to each regional apparatus organization within the work environment of the Regional Government of the City of Banjar including the Regional Secretariat of the City of Banjar. The purpose of this study was to analyze the implementation of the Core Value ASN work culture implementation BerAKHLAK at the Banjar City Regional Secretariat. The research method used is a descriptive method with a qualitative approach. Data collection techniques are observation, interviews, documentation, and literature studies. Based on the results of the research, the implementation of the work culture of the Core Values of ASN with Morals at the Regional Secretariat of the City of Banjar has gone quite well, however, it is necessary to increase employee awareness and joint commitment in implementing the work culture of the Core Values of ASN BerAHLAK at the Regional Secretariat of the City of Banjar. Keywords; Implementasi; Budaya Kerja; BerAKHLAK